2015
DOI: 10.1055/s-0035-1565204
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Rest Heart Rate in Psychiatric Patients and Different Effects of Psychotropic Medication

Abstract: The elevated RHR in psychiatric patients is a common phenomenon and can be observed independently of the use of psychotropic medication but more in patients with schizophrenia. An interesting additional finding could be a possible protective effect of SSRI on RHR in psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…There were studies that heart rate has increased as people gain weight [ 9 10 ]. Conversely, recent study showed that the presence or absence of obesity did not affect RHR in patients with schizophrenia [ 11 ]. In any case, the change in body weight did not affect RHR in this study.…”
Section: Discussionmentioning
confidence: 98%
“…There were studies that heart rate has increased as people gain weight [ 9 10 ]. Conversely, recent study showed that the presence or absence of obesity did not affect RHR in patients with schizophrenia [ 11 ]. In any case, the change in body weight did not affect RHR in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Most SSRIs have been associated with a reduction in basal heart rate [70,71,72], even though a recent large study has found the opposite (an increase in heart rate associated with the use of SSRIs) [73]. On the contrary, the use of SNRIs (e.g.…”
Section: Cardiovascularmentioning
confidence: 99%
“…Possibly but physical assessment of the acutely mentally ill consumer is important as nearly half the texts suggested. Furthermore, as vital signs can change in response to medication, administration such as antipsychotics (Sarlon et al., 2016), the importance of measuring these signs should be highlighted in mental health nursing textbooks. Only one of the reviewed texts mentioned this (Jones & Beauvais, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Within the mental health setting, vital signs assessment might be neglected because abnormal vital sign ranges can be less clinically meaningful due to the use of psychotropic medication or because consumers' heart rate and blood pressure are often abnormal (Alvares et al., 2016; Sarlon et al., 2016). In an Australian study of 70 mental health nurses, reasons for missed nursing care also included inadequate staffing and the increased physical needs and acuity of consumers (Joseph et al., 2022).…”
Section: Introductionmentioning
confidence: 99%